Bringing a socially assistive robot to the paediatric emergency department: design, development, and usability testing - Foster, Mary Ellen; Stinson, Jennifer N.; Harris, Lauren; Kim, Kate Kyuri; Litwin, Sasha; Candelaria, Patricia; Hudson, Summer; Leung, Julie; Petrick, Ronald P. A.; Lindsay, Alan; Ramírez-Duque, Andrés; Smith, David Harris; et al. (Frontiers in Robotics and AI, 2025)
IntroductionChildren undergoing medical procedures in paediatric Emergency Departments (EDs) often experience significant pain and distress. Socially Assistive Robots (SARs) offer a promising avenue for delivering distraction and emotional support in these high-pressure environments. This study presents the design, development, and formative evaluation of an AI-enhanced SAR to support children during intravenous insertion (IVI) procedures.MethodsThe robot system was developed through a participatory design process involving healthcare professionals, patients, caregivers, and interdisciplinary research teams. The SAR was designed to autonomously adapt its behaviour to the child’s affective state using AI planning and social signal processing. A two-cycle usability study was conducted across two Canadian paediatric EDs, involving 25 children and their caregivers. Feedback was collected through observations, interviews, and system logs.ResultsThe SAR was successfully integrated into clinical workflows, with positive responses from children, caregivers, and healthcare providers. Usability testing identified key technical and interaction challenges, which were addressed through iterative refinement. The final system demonstrated robust performance and was deemed ready for a formal randomised controlled trial.DiscussionThis work highlights the importance of co-design, operator control, and environmental adaptability in deploying SARs in clinical settings. Lessons learned from the development and deployment process informed six concrete design guidelines for future SAR implementations in healthcare.